PENGARUH STATUS SOSIAL EKONOMI ORANGTUA DAN HASIL BELAJAR EKONOMI TERHADAP LITERASI EKONOMI DI SMP NEGERI 43 SURABAYA - Ernawati, Lilik (UNIVERSITAS NEGERI SURABAYA, 2017)
This research to know socio economic status influence socio economic status and learning outcome economy by partial and together to literacy VIII SMPN class student's economy 43 Surabaya. The research is quantitative approach. Total Sample as much as 176 VIII class student from population total of 314 students. Research result indicate that the economic and social status of the study results in significant economic literacy on partial and together, it means that parents and socio economic status in both high economic study results will boost the knowledge and economic literacy.